Pengaruh Persepsi Manfaat Dan Kemudahan Terhadap Minat Konsumen Dalam Menggunakan Qris (Studi Kasus Masyarakat Kecamatan Pangkalan Kuras, Provinsi Riau) - Heppi, Heppi; Lestari, Indawati (Universitas Medan Area, 2024)
The aim of this research is to explore the impact of perceived benefits and convenience on consumer interest in using QRIS, with a focus on the people of Pangkalan Kuras District, Riau Province. This research uses a quantitative type of approach. The population in the research is the people of Pangkalan Kuras District, Riau Province who use QRIS as a payment transaction tool as many as 64,862 people. The sampling method used was probability sampling. The sampling technique used in this population was accidental sampling technique and the number of respondents involved was 100 people. selected from Pangkalan Kuras District. Data was collected through questionnaires as a primary data source and then analyzed using multiple linear regression analysis. The results of hypothesis testing show that Perceived Benefits (X1) has a positive and significant influence on consumer interest in using QRIS. Convenience (X2) also has a positive and significant influence on consumer interest in using QRIS. Both Perceived Benefits and Convenience show a positive and significant influence on consumer interest in using QRIS.